2017
DOI: 10.1038/cddis.2017.184
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced neuroprotective efficacy of bone marrow mesenchymal stem cells co-overexpressing BDNF and VEGF in a rat model of cardiac arrest-induced global cerebral ischemia

Abstract: Cardiac arrest-induced global cerebral ischemia injury (CA-GCII) usually leads to a poor neurological outcome without an effective treatment. Bone marrow-derived mesenchymal stem cells (BMMSCs) may provide a potential cell-based therapy against neurologic disorders through induction of brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF). To optimize the neuroprotective efficacy of BMMSCs further, in this study we have derived BMMSCs, which co-overexpress both BDNF and VEGF, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…Administration of adenovirus‐transfected BDNF‐overexpressing MSCs through intracerebral transplantation or intranasal delivery9b has been demonstrated to reduce neurological deficits after cerebral ischemia. More recently, lentivirus‐transfected MSCs also showed the potential to treat cerebral ischemia through a less invasive venous approach . However, to the best of our knowledge, non‐viral system, that can successfully engineer MSCs for efficient therapy post‐ischemic stroke via intravenous administration, has never been reported yet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of adenovirus‐transfected BDNF‐overexpressing MSCs through intracerebral transplantation or intranasal delivery9b has been demonstrated to reduce neurological deficits after cerebral ischemia. More recently, lentivirus‐transfected MSCs also showed the potential to treat cerebral ischemia through a less invasive venous approach . However, to the best of our knowledge, non‐viral system, that can successfully engineer MSCs for efficient therapy post‐ischemic stroke via intravenous administration, has never been reported yet.…”
Section: Resultsmentioning
confidence: 99%
“…BDNF has been proved as one of the essential neurotrophic factors that is beneficial for post‐ischemic stroke recovery, due to its critical role in neuroprotection and neurogenesis, as well as angiogenesis . Currently, genetic manipulation of MSCs using virus is the main strategy to gain hypersecretion of BDNF 9b,10. However, viral‐based genetic engineering is presently restricted due to their safety concerns .…”
Section: Introductionmentioning
confidence: 99%
“…Although all four analytes fall into the category of mainly pro‐inflammatory effectors, some studies have provided evidence of their pleotropic, antiinflammatory, and neuroprotective roles. IL‐6 is suggested to have antiinflammatory properties with enhancing neurogenesis abilities in the CNS While IL‐8 and VEGF are potent angiogenic factors with a recently investigated neuroprotective effect, some evidence has also supported the neuromodulatory effects of MCP‐1 in the CNS . Despite this similar trend, the concentration of the top analytes produced varied greatly between patients.…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs transplantation therapy is promising in mitigating the extent of SCI, not only due to a favorable ethical profile and safety, but also due to providing beneficial effects on various postinjury aspects: inflammation, apoptosis, axonal regrowth, angiogenesis, tissue sparing, astroglial scar, and motor recovery . It is well known that BMSCs secrete a large variety of molecules and many studies have shown beneficial impacts from these factors such as brain‐derived neurotrophic factor (BDNF), nerve growth factor (NGF), vascular endothelial growth factor (VEGF), insulin‐like growth factor (IGF), epidermal growth factor (EGF), and more …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] It is well known that BMSCs secrete a large variety of molecules and many studies have shown beneficial impacts from these factors such as brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), vascular endothelial growth factor (VEGF), insulin-like growth factor (IGF), epidermal growth factor (EGF), and more. [13][14][15][16][17][18][19] Previously, neurotrophin and physical stimulation were commonly employed to enhance the effect of BMSCs. Specifically, low-intensity pulsed ultrasound (LIPUS), as a physical stimulation, appeared to be an effective assistant method.…”
Section: Introductionmentioning
confidence: 99%